2013
DOI: 10.1159/000355622
|View full text |Cite
|
Sign up to set email alerts
|

Tuebingen CD-25 Is a Sensitive Tool to Investigate Health-Related Quality of Life in Cushing's Disease Patients in the Course of the Disease

Abstract: Background: The primary object was to investigate whether the Tuebingen CD-25 captures changes in health-related quality of life (HRQoL) sensitively in Cushing's disease (CD) and to identify factors that favour postoperative HRQoL. Methods: 17 CD patients were scheduled for transsphenoidal tumour removal and filled out the inventory before and after surgery. The mean time elapsed after surgery was 14.4 ± 11.3 months. All patients were in remission at the second timepoint of investigation. Results: HRQoL as ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…The following independent variables: age, presence of comorbidities, presence of hypocortisolism, presence of hypopituitarism, time to diagnosis, time since surgery and postoperative radiotherapy were included in the model. The rationale of the chosen factors for the regression analyses were that previous studies already discussed effects of hypopituitarism (here also including replacement of glucocorticoids) [17] and comorbidities [18] on either psychiatric status or quality of life in CD. Pituitary radiation was shown to have little [19] or no effect [17,20,21] on quality of life outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following independent variables: age, presence of comorbidities, presence of hypocortisolism, presence of hypopituitarism, time to diagnosis, time since surgery and postoperative radiotherapy were included in the model. The rationale of the chosen factors for the regression analyses were that previous studies already discussed effects of hypopituitarism (here also including replacement of glucocorticoids) [17] and comorbidities [18] on either psychiatric status or quality of life in CD. Pituitary radiation was shown to have little [19] or no effect [17,20,21] on quality of life outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Only the presence of comorbidities, and in one domain pituitary deficiencies, was associated with psychopathological status, strongly suggesting that the stressors female CD patients have to cope with play the main role in the pathogenesis of psychiatric disorders. In our previous study we identified variables that predict several domains of postoperative quality of life, one of them being depression [18]. We observed in a cohort of 17 patients (of whom 82.4% were female) that postoperative depression scores were best predicted by the number of postoperative comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Impairments concerning the HRQoL have been increasingly recognized as an important aspect of clinical management in patients suffering from CD [3], as HRQoL among CD patients is reduced compared to the general population. Approximately 80% of patients with active CD suffer from impairments in HRQoL compared to age- and sex-matched healthy controls [4,5]. Postoperatively, one third of all CD patients continue to suffer from impaired HRQoL despite biochemical remission [5], which is attributed to irreversible effects caused by glucocorticoid excess [6].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of patients with active CD suffer from impairments in HRQoL compared to age- and sex-matched healthy controls [4,5]. Postoperatively, one third of all CD patients continue to suffer from impaired HRQoL despite biochemical remission [5], which is attributed to irreversible effects caused by glucocorticoid excess [6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation